Legal implications of UNESCO resolutions on al-Quds - Elshobake, Mohammed R. M. (Diyanet İşleri Başkanlığı, 2022)
Al-Quds has a great religious status, in addition to its historical status through the ages, and its civilizational and cultural status. The legal status of al-Quds has been the subject of legal debate since the United Nations General Assembly issued Partition Resolution No. (181) of 1947, which considered the city of al-Quds to be a separate entity subject to an international system administered by the United Nations through the trusteeship Council. Since then, many international resolutions related to the city of al-Quds have been issued, and this holy city has been subjected to multiple forms of grave aggression in violation of the rules of international law by the Israeli occupation from 1948 until the present day. The United Nations Educational, Scientific, and Cultural Organization (UNESCO) issued a number of resolutions related to al-Quds and its holy places. The decisions focused on of the city of al-Quds, cancelling what Israel changed there, and preserving cultural property, holy places, and educational aspects. Following the inductive and analytical approaches, this research paper aims to clarify the decisions of the United Nations Educational, Scientific and Cultural Organization (UNESCO) related to al-Quds, in addition to explaining the legal implications of those decisions. The benefit of this paper is to highlight the legal status of the city of al-Quds and its holy places, and to come up with recommendations that contribute to preserving the religious and cultural heritage of the city of al-Quds.